2018
DOI: 10.5606/tftrd.2018.2672
|View full text |Cite
|
Sign up to set email alerts
|

The effects of body weight-supported treadmill training on static and dynamic balance in stroke patients: A pilot, single-blind, randomized trial

Abstract: Objectives: This study aims to compare effectiveness of isolated body weight-supported treadmill training (BWSTT) with conventional and combined training on balance, mobility, and fear of falling in stroke patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 32 publications
(40 reference statements)
1
36
0
Order By: Relevance
“…The methodological quality of the studies included in this review was globally more than acceptable (average total score 5.5 ± 1.0, range 4–7). Here, 46.2% of trial reports are moderate to high quality, scoring ≥6/10 on the PEDro scale ( 34 , 37 , 38 , 40 , 41 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The methodological quality of the studies included in this review was globally more than acceptable (average total score 5.5 ± 1.0, range 4–7). Here, 46.2% of trial reports are moderate to high quality, scoring ≥6/10 on the PEDro scale ( 34 , 37 , 38 , 40 , 41 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…In all studies, the results of the intergroup comparison were reported for at least one of the main outcome measures. Mean and variability data for at least one of the main outcome measures were reported in 11 (84.6%) studies ( 31 34 , 36 41 , 43 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations